Pembahasan Soal-Soal Program Linear dengan Menggunakan Metode Campuran - Irfi Windari; Sabila Yusma Al Wahida; Maya Hania Salsabila; Dedek Kustiawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The problem of linear programming is a linear problem to determine the magnitude of the value of each variable so that the value of the objective function or objective can be optimum, namely by maximizing or minimizing. To solve linear programming problems, a mixed method can be used, namely a method that combines two methods at once, namely the elimination method and the substitution method. The elimination method is a method that eliminates variables by adding or subtracting two equations that have the same coefficient. While the substitution method is the replacement of a variable with a variable from another equation.